1979
DOI: 10.1002/app.1979.070230823
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking aqueous poly(vinyl pyrrolidone) solutions by persulfate

Abstract: SynopsisAqueous solutions with 1.5 to 6.5 wt-% poly(viny1 pyrrolidone), PVP, are converted to stable gels by reaction with potassium persulfate. Large quantities of persulfate are needed for high-modulus gels, 50% to 150% of the weight of PVP being required typically. The shear modulus G' can be measured during reaction by making the gel the restoring element in a simple torsion pendulum. The increase in modulus to a maximum plateau value of GLm can be expressed as a first-order process:where t is elapsed time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 3 publications
3
50
0
Order By: Relevance
“…Similar hydrogen bonding might exist in the aqueous salt solutions of the PO~, HPO4, H2PO4 anions. Direct binding of the polyvalent ions cause a gel formation similar to that observed in PVP in aqueous salt solution of K2S208 [30]. With the salts used in this study we have not observed any gel formation.…”
Section: Discussionsupporting
confidence: 65%
“…Similar hydrogen bonding might exist in the aqueous salt solutions of the PO~, HPO4, H2PO4 anions. Direct binding of the polyvalent ions cause a gel formation similar to that observed in PVP in aqueous salt solution of K2S208 [30]. With the salts used in this study we have not observed any gel formation.…”
Section: Discussionsupporting
confidence: 65%
“…The subsequent crosslinking of linear PVP is achieved, for example, by yradiation13 or by treatment of the polymer with persulphate 14 or with hydrazine and hydrogen peroxide15 or with l)(,w-diolefines in the presence of peroxides. 16 The products obtained are only slightly cross-linked and form soft gels in solvents dissolving linear PVP.…”
Section: Cross-linked Poly-vinylpyrrolidonementioning
confidence: 99%
“…It is known that the aqueous solutions of PVP are converted to stable gels by the reaction with K 2 S 2 O 8 . 29,30 However, the mechanism of PVP/K 2 S 2 O 8 linkage is not known exactly and it is also reported that in addition to intermolecular crosslinking processes, chain scission, and other competing reactions may take place in aqueous solutions. The most interesting feature of gelation of PVP with persulfate is the requirement of an extremely high concentration of persulfate to form the network structure.…”
Section: Resultsmentioning
confidence: 98%